Bottlenecks aligning UX design with user psychology - Evans, David C. (Apress, 2017)
Learn the psychological constrictions of attention, perception, memory, disposition, motivation, and social influence that will determine whether customers will be receptive to your digital innovations. Bottlenecks: Aligning UX Design with User Psychology fills a need for entrepreneurs, designers, and marketing professionals in the application of foundational psychology to user-experience design. The first generation of books on the topic focused on web pages and cognitive psychology. This book covers apps, social media, in-car infotainment, and multiplayer video games, and it explores the crucial roles played by behaviorism, development, personality, and social psychology. Author David Evans is an experimental psychology Ph. D. and senior manager of consumer research at Microsoft who recounts high-stakes case studies in which behavioral theory aligned digital designs with the bottlenecks in human nature to the benefit of users and businesses alike. Innovators in design and students of psychology will learn: The psychological processes determining users? perception of, engagement with, and recommendation of digital innovations Examples of interfaces before and after simple psychological alignments that vastly enhanced their effectiveness Strategies for marketing and product development in an age of social media and behavioral targeting Hypotheses for research that both academics and enterprises can perform to better meet users? needs.
Includes index. - Includes bibliographical references and index. - Online resource; title from PDF title page (SpringerLink, viewed February 21, 2017)
Keywords: Human-computer interaction; User-centered system design; Web sites; Design; User interfaces (Computer systems); Design; Human-computer interaction; Psychological aspects; Conception participative (Conception de systèmes); Psychology; Society & social sciences; Media studies; Games development & programming; User interface design & usability; COMPUTERS; Computer Literacy; COMPUTERS; Computer Science; COMPUTERS; Data Processing; COMPUTERS; Hardware; General; COMPUTERS; Information Technology; COMPUTERS; Machine Theory; COMPUTERS; Reference; Computers and IT